Entrepreneurship as a Lever for Growth and Endogenous Development in Low-Density Territories (Global Journal of Human-Social Science, 2023)
From the analysis of GEM data in relation to the Portugal-Spain border space more specifically Alentejo-Extremadura we tried to assess whether the development of entrepreneurial activities was affected by its territorial context This being one of the least developed borders in the whole European Union EU and a problem for territorial cohesion leading to the definition of policies and lines of support for its development we try to understand whether entrepreneurship a major factor in the development of the territory followed the position of the respective countries or if there is a divergent performance Entrepreneurship increasingly pointed out as a means of enhancing the development of regions either through job creation or through innovation allows the inversion of the vicious cycle of low-density territories The study of entrepreneurship in these regions important for the perception of the relevant variables of this dynamic is fundamental in this region in particular since it is one of the regions of the EU with the lowest socio-economic development rates being pointed out as an area of low density in which entrepreneurial captivity may be the driving force behind this situation
Keywords: frontier; entrepreneurial activity; gem; territorial cohesion; regional development